2014
DOI: 10.1177/2325957414527167
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Second-Line Antiretroviral Therapy in Resource-Limited Settings

Abstract: There is limited information on efficacy and durability of second-line antiretroviral therapy (2NL) beyond 12 months in resource-limited settings. A total of 73 patients were enrolled into a prospective 2NL observational cohort in Nigeria. Second-line antiretroviral therapy consisted of lopinavir/ritonavir plus nucleoside reverse transcriptase inhibitors. Time on 2NL ranged from 15 to 31 months. Genotypes were retrospectively done and not available to guide second-line regimen choice. At enrollment, median CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Patients with higher viral loads and lower CD4 counts at the time of switch to second line were at greater risk for attrition and were less likely to experience virologic suppression. These findings are similar to those reported elsewhere, but the larger sample size and longer follow‐up time aid in making inferences . While drug resistance testing is not routinely conducted, previous research has shown that suboptimal adherence is likely to be the primary driver of virologic failure on second‐line ART .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Patients with higher viral loads and lower CD4 counts at the time of switch to second line were at greater risk for attrition and were less likely to experience virologic suppression. These findings are similar to those reported elsewhere, but the larger sample size and longer follow‐up time aid in making inferences . While drug resistance testing is not routinely conducted, previous research has shown that suboptimal adherence is likely to be the primary driver of virologic failure on second‐line ART .…”
Section: Discussionsupporting
confidence: 86%
“…Numerous programmes in resource‐limited settings have demonstrated successful treatment outcomes of first‐line therapy. Fewer, however, have described the treatment outcomes of second‐line therapy, with evidence mainly restricted to smaller cohorts with limited information on efficacy and durability of second‐line ART beyond 1 year . Nonetheless, programmes that have reported outcomes have shown mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…This study was the first to identify and analyse DRMs in HIV-infected patients failing second-line ART regimens in Rwanda. Little data exists for DRMs in patients failing second-line ART in Africa [4,6]. Of patients with successful genotype analyses, more than one-third demonstrated no evidence of resistance, while 30% had DRMs to at least one class of ARVs.…”
Section: Discussionmentioning
confidence: 99%
“…However, as in other resource-limited settings (RLS), viral load (VL) monitoring during the initial scale-up period was not routinely available. Patients failing first-line ART regimens were at risk of acquisition and accumulation of HIV drug resistance mutations (DRMs) that could compromise effectiveness of secondline ART regimens [2][3][4].…”
mentioning
confidence: 99%
“…Viral failure was identified less often than one might expect from other second-line studies, 20–25 particularly when considering the long follow-up period of this analysis. However, the low frequency of viral load measurements, which was only done in 55% of participants, meant that this is likely to be an underestimate of the true proportion of the cohort that had viral failure.…”
Section: Discussionmentioning
confidence: 73%